NARASI GERBANG RUMAH PERANAKAN DI PECINAN, LASEM, JAWA TENGAH: PENDEKATAN FENOMENOLOGI - Darmayanti, Tessa Eka; Bahauddin, Azizi (architecture department, Engineering faculty, Universitas Diponegoro, 2020)
The gate is an important component of Peranakan houses in Lasem. They are included in the cultural heritage of Indonesia, and most of them are more than a hundred years old, but still stand firm and lined up neatly adorning the Pecinan area. The purpose of this paper is to provide a different perspective on the existence of the Peranakan houses’ gates that interpreted through the author’s experiences during the fieldwork. The gate embodiment gives a different atmosphere and experience which is not found elsewhere because they are unique and irreplaceable. Unfortunately, preserving these gates become a serious challenge in the modern era. The finding comes from the phenomenon which found after the field research and analyzed using the phenomenology approach of Merleau Ponty, Juhani Pallasmaa, and Steven Holl. Phenomenology allows people to express their existence through architecture and let its value appear to people as they experience it. The result showed that experiences would give the people have an attachment to the place unconsciously.